RELATIONSHIP OF GREEN PSYCHOLOGICAL CLIMATE AND GREEN ORGANIZATIONAL BEHAVIOR: THE CASE OF HOTEL BUSINESSES - Yaşar, Emre (Fırat Üniversitesi, 2023)
As a result of increasing negativities in environmental issues, interest in green practices has increased. This interest is not limited to the application only. At the same time, green practices have become the focus of academic studies. This research aims to examine the effect of green psychological climate perception on the green organizational behavior of employees in hotel businesses. The quantitative research method was adopted as part of the research aim. The study universe consists of workers in hotel businesses in Antalya. The research sample comprises employees of 5-star hotel businesses in Antalya. The questionnaire form was applied with the judgmental sampling technique. Data was collected between August 1 and September 1, 2022. Between these dates, a total of 400 questionnaires were reached. However, the search analysis was carried out using 370 questionnaires. Following the study, the green psychological climate significantly impacted green organizational behavior and sub-dimensions. Green psychological climate and green organizational behavior do not differ significantly in terms of gender variable. Green organizational behavior is affected considerably in terms of marital status, age, education level, work time, and department variables.

Çevresel konularda artan olumsuzluklar sonucunda yeşil uygulamalara yönelik ilgi artmıştır. Bu ilgi sadece uygulama ile sınırlı kalmamıştır. Aynı zamanda akademik anlamda yapılan çalışmalarda da yeşil uygulamalar odak noktası haline gelmiştir. Bu araştırmanın amacı otel işletmelerindeki yeşil psikolojik iklim algısının işgörenlerin yeşil örgütsel davranışı üzerindeki etkisini incelemektir. Araştırmanın amacı kapsamında nicel araştırma yöntemi benimsenmiştir. Araştırmanın evrenini Antalya’daki otel işletmelerindeki işgörenler oluşturmaktadır. Araştırmanın örneklemini ise Antalya’daki 5 yıldızlı otel işletmelerindeki işgörenler oluşturmaktadır. Anket formu yargısal örnekleme tekniğiyle uygulanmıştır. Veri toplama 1 Ağustos- 1 Eylül 2022 tarihleri arasında gerçekleştirilmiştir. Bu tarihler arasında toplam 400 anket formuna ulaşılmıştır. Fakat araştırma analizi 370 anket formu ile yapılmıştır. Gerçekleştirilen analizler sonucunda yeşil psikolojik iklimin yeşil örgütsel davranışı ve alt boyutlarını anlamlı bir şekilde etkilediği belirlenmiştir. Cinsiyet değişkeni açısından yeşil psikolojik iklim ve yeşil örgütsel davranış anlamlı bir şekilde farklılaşmamaktadır. Medeni durum, yaş, eğitim düzeyi, çalışma süresi ve departmanı açısından yeşil örgütsel davranış anlamlı bir şekilde farklılaşmaktadır.
Yeşil Psikolojik İklim ve Yeşil Örgütsel Davranış İlişkisi: Otel İşletmeleri Örneği